Circulating tetrahydrobiopterin as a novel biomarker for abdominal aortic aneurysm - Siu, Kin Lung (Am J Physiol Heart Circ Physiol, 2014)
Rupture of abdominal aortic aneurysm (AAA) is unpredictable and lethal. A clinically valid biomarker to monitor the disease has not been available. Based on our recent discoveries that uncoupled endothelial nitric oxide synthase (eNOS)/tetrahydrobiopterin deficiency plays a causal role in various models of AAA, the present study examined the relationship between circulating and tissue levels of tetrahydrobiopterin (H(4)B) in angiotensin II-infused hyperphenylalaninemia (hph-1) and apoE null mice. For apoE null mice, tissue and plasma H(4)B levels decreased time dependently, to 2.69 ± 0.15 and 1.99 ± 0.06 pmol/mg, respectively (from 4.86 ± 0.32 and 3.31 ± 0.13 pmol/mg at baseline) by week 3, when aneurysms developed. For hph-1 mice, tissue and plasma H(4)B levels decreased significantly to 1.02 ± 0.10 and 0.98 ± 0.09 pmol/mg, respectively (from 1.84 ± 0.18 and 1.48 ± 0.12 pmol/mg at baseline), by week 1, when aneurysms developed. Oral folic acid administration, which has been shown to improve aortic H(4)B levels to completely prevent or markedly decrease the incidence of AAA, significantly increased tissue and plasma H(4)B levels in both animal models starting at week 1. The two H(4)B measurements at all conditions showed significant linear correlation, suggesting that plasma H(4)B accurately predicts its tissue levels when H(4)B is either reduced or enhanced. Together, these data demonstrate that H(4)B levels decrease with AAA development and increase with folic acid treatment in two different murine models of AAA and that plasma H(4)B levels accurately reflect H(4)B levels in the tissue, suggesting that circulating H(4)B levels may be used clinically as a novel and powerful biomarker for the development and response to treatment of AAA.